The HUBUNGAN ANTARA KETERAMPILAN BERBICARA (PUBLIC SPEAKING) DENGAN KEPERCAYAAN DIRI SISWA SMPN 3 NATAR - Triyani, Riska Sukma; Putri, Tania Aurellia; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research aims to determine the relationship between public speaking skills and the self-confidence of class VIII students at SMPN 3 Natar. The research method used is the correlation method with a quantitative approach. The population of this study consisted of 30 students, and all of them were sampled using saturated sampling techniques. Data was collected through a self-confidence questionnaire and a public speaking ability test which includes four indicators, namely courage to introduce oneself, appearing in front of the class, telling stories with gestures, and telling stories with facial expressions. The research results show that students' self-confidence level is in the "sufficient" category with a percentage of 59%, and their public speaking skills are also in the "sufficient" category with a percentage of 70%. The Spearman Rank correlation test produces a significance value of 0.042 <0.05, which means there is a significant relationship between self-confidence and students' public speaking abilities. Thus, the higher the student's level of self-confidence, the better their ability to speak in public.